Dimensões subjetivas da experiência do abuso de substâncias psicoativas por usuários do centro de atenção psicossocial em álcool e outras drogas de São Carlos - Silva, Pedro de Oliveira Fernandes da (Universidade Federal de São Carlos, 2025)
The consumption of psychoactive substances (PAS) permeates the constitution of humanity, starting from a practice of altering the state of consciousness to a way of dealing with discomfort. In this way, a set of issues of public health order is built around these substances, due to their intoxicating potential. This made it necessary to create specialized care strategies that had adequate care techniques to meet the mental health demands of users, materialized in CAPSad and in the harm reduction model. Even so, as substance abuse is constituted by the interaction of psychosocial determinants and the unconscious structure of the relationship that the user establishes with the substance, it describes an essentially unique process that must be treated as such. Therefore, the objective of this study was to investigate the subjective dimensions in the experience of psychoactive substance abuse by users of the CAPSad in the municipality of São Carlos. To this end, this social psychology in health research was constructed, of an empirical and qualitative-interpretative nature, which included the participation of 12 users of the CAPSad in São Carlos (24 to 61 years old, 9 men and 3 women) through the McGill Illness Narrative Interview (MINI). The participants also answered a questionnaire for the characterization of abuse, and a script was used for the analysis of data from their medical records. The research data were analyzed using thematic content analysis in the hermeneutic-dialectical approach. Key conclusions include: the experience of abuse is impacted by the user's life history and is unique through the rituals, gains, and losses of the harmful consumption of psychoactive substances; users attribute particular meanings to their own experience of abuse, its genesis, and the possibility of treatment. The production of the participants' subjectivity is traversed by agencies of guilt and shame that associate their way of existing with exclusion, loss of autonomy, and illness. Substance abuse was characterized by several psychosocial determinants of the health and illness process, pointing to the subject's vulnerability to this type of abuse, and the experience of treatment for abuse influences the production of diseased subjectivities. These conclusions indicate the need for specialized health care services such as CAPSad to prioritize, in team work planning, this dimension of singularity in the modes of substance abuse, in conjunction with the psychosocial determinants of the health and disease process. This confirms the relevance of the individualized therapeutic project (PTS) as a powerful technology for organizing mental health care, as it guarantees a comprehensive and individualized approach by encompassing aspects of care, education, and management of work in health.
Subjective dimensions of the experience of psychoactive substance abuse among users of the psychosocial care center for alcohol and other drugs in São Carlos
Keywords: Abuso de substâncias; Subjetividade; Saúde mental; Pesquisa qualitativa; Atenção psicossocial; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA; 3. Saúde e Bem-Estar